Linear and Non-Linear Static Progressive Collapse Analysis of Steel Framed Buildings with I-Beams and Truss Beams - İlman, Buğse (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Progressive collapse is the collapse of a considerably large part of a structure as a result of failure of its relatively small part. After the progressive collapse (PC) of the Ronan Point apartment tower in England in 1968, prevention of progressive collapse became one of the challenges of structural engineers. Since then, researchers carried out many studies on progressive collapse. In addition, General Services Administration (GSA), Department of Defense (DoD), and Unified Facilities Criteria (UFC) developed guidelines for assessing and preventing progressive collapse. Furthermore, NIST (National Institute of Standards and Technology) has published a list of potential load hazards that might generate progressive collapse. This study used GSA guidelines to investigate the progressive collapse potential of an eight story steel framed building by using I-beams and trusses as floor beams. Linear and nonlinear static analysis were used to assess the potential of PC by using the general purpose computional analysis program ETABS. Structural members PC potential is assessed according to Demand Capacity Ratio (DCR) for linear static analysis and rotation for nonlinear static analysis. The results show that, after removing the columns for linear static analysis, floors with truss beams had DCR values less than the floor with I-beams. The results of nonlinear static analysis indicate that the floors with I-beams had greater rotation values than the floors with truss beams. As part of Alternative Path Method, new bracings introduced in the bay adjacent to the removed column to rehabilitate the buildings.

ÖZ: Aşamalı çöküşün başlamasına neden genelde lokal hasarlardır. Bunun yanı sıra birkaç elemanın kırılışı sonucu yapının daha büyük bir kısmının çökmesi de aşamalı çöküşün başlamasının nedenlerinden biridir. Yakın zamanlarda meydana gelen ABD’de Ticaret Merkezi binasının aşamalı çöküşü gibi felaketlerin olasılığını azaltmak ve önlemek için yapı analizi ve tasarımı yapılırken bir dizi önlemlerin alınması artık ihtiyaç olmuştur. Buna ek olarak, yapıların aşamalı çöküşe karşı dayanımını artırma yöntemleri araştırılabilir. Bu araştırmada I-kirişi ve kafes kiriş döşeme sistemi olan çelik karkas yapılarda aşamalı çöküş potansiyeli araştırılmıştır. Bu nedenle bahsekonu çelik karkas yapıda doğrusal statik ve doğrusal olmayan statik analiz metodları ile aşamalı çökme potansiyeli etkisi araştırılmıştır. Genel Hizmet İdaresi (GSA) ilkeleri, doğrusal statik analiz metodu ve doğrusal olmayan statik analiz metodu kullanılarak yapı analiz edilmiştir. Doğrusal statik analiz metodu sonuçlarına göre I-kirişli döşemeli yapıların tüm kiriş açıklıklarında aşamalı çöküş potansiyeli kafes kiriş döşemeli yapılara göre daha fazladır. Buna ek olarak, doğrusal olmayan statik analiz sonuçlarına göre kafes kiriş döşemeli yapıların tüm kiriş açıklıklarında aşamalı çöküş potansiyeli I-kirişli döşemeli yapılara göre daha azdır. Tüm yapısal elemanların, doğrusal statik analizinden DCR değerleri ve doğrusal olmayan statik analizinden rotasyon değerleri bulunmuştur. Daha sonra kabul değerlerini geçen tüm elemanlar için kolon eksiltilen bölgeye komşu bölgede yeni destek sistemi kullanılarak yapısal elemanlar rehabilite edilmiştir.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2017. Supervisor: Assoc. Prof. Dr. Mürüde Çelikağ.
Keywords: Building, Iron and steelxSteel, Structural; Structural stability; Structural failures--Structural failures - Prevention--Structural dynamics--Structural design; Progressive collapse; linear static analysis; nonlinear static analysis; truss beams; I-beams; Civil Engineering